Fear, estrangement and family projects in the immigrant Venezuelan population in Peru - Loayza, Jerjes (2021)
This article analyzes the fears and concerns many Venezuelan immigrants living in Peru go through every day. It delves into the communication dynamics between Peruvians and Venezuelans, as well as into its consequences at an intersubjective level. Methodologically, it is based on data gathered from interviews in Ayacucho, Chiclayo, Cusco and mainly in Lima. Basically, the life histories of immigrants in vulnerable situation are analyzed, whether they are unemployed, asking for financial support on the street or having undergone any difficult experience. Finally, the expectations they hold on the future are joined together, identifying a series of hopes they embrace to survive to the exploitation and discrimination they would face. However, this study still addresses the encouraging frameworks in a country that, as it is understood, is still an important migration destination for them.